Pengaruh Pelatihan, Kompensasi Dan Ketepatan Waktu Terhadap Kinerja Driver Go-Jek Medan Polonia - Firmansyah, Firmansyah; Hidayat, Toni (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study analyzes the effect of training, compensation and timeliness on the performance of Go-Jek Medan Polonia drivers. The research method used in this research is descriptive quantitative. The population in this study were 177 Go-Jek Medan Polonia Drivers. The analytical method used was multiple linear regression using the SPSS program. The results of this study indicate that the t-count > t-table (2.917 > 1.6690) means that training has a significant effect on performance, so Ha1 is accepted. The value of t-count > t-table (3.558 > 1.6690) and significant means that compensation has a significant effect on customer loyalty on performance, then Ha2 is accepted. The value of t-count > t-table (3.437 > 1.6690) and significant means that timeliness has a significant effect on customer loyalty on performance, then Ha3 is accepted. Fcount value (43.811) > Ftable (2.76), and a significance value of 0.000 <0.05, it can be concluded that the fourth hypothesis is accepted, meaning that the Training Variables (X1), Compensation (X2), and Timeliness (X3) influence simultaneously (simultaneous) to the Performance Variable (Y)